THE PARADOX OF SPORT: THE BENEFICIAL EFFECTS OF PHYSICAL ACTIVITY ON THE CARDIOVASCULAR SYSTEM VERSUS THE RISK OF ARRHYTHMIA - Alicja Babula; Bartosz Golis; Anna Maria Gęsińska; Krystian Czyżykowski; Helena Szelka; Paweł Edyko; Wiktor Golus; Katarzyna Andrzejewska; Zuzanna Przybyła; Hubert Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
In recent years, sport has become increasingly popular. It has long been known that regular physical activity is one of the most important factors in preventing cardiovascular disease. Many studies show that systematic exercise has many benefits: it leads to lower blood pressure, improved lipid profile, and beneficial adaptations in the structure and function of the heart. Endurance training induces physiological remodeling of the heart muscle, including enlargement of its chambers, increased left ventricular mass, and improved oxygen efficiency. This results in more efficient blood flow, lower resting heart rate, and increased heart rate variability. These parameters are an indicator of good autonomic balance. However, over the years, we have seen increasing evidence that long-term, intense endurance training may carry certain risks. Numerous studies indicate an increased risk of arrhythmia in people who engage in intense sports. The most commonly described rhythm disorder in this population is atrial fibrillation, the incidence of which in endurance athletes may be several times higher than in the general population. Some retired athletes also experience cases of ventricular tachyarrhythmia, probably due to right ventricular overload and remodeling processes.